A Letter to the Editor on the Importance of a Control Group in Sleep Research - Shadi Naderyan Fe'li (Journal of Sleep Sciences)
In this letter, the necessity of a control group in sleep studies is emphasized. Indeed, I believe that it is crucial to follow a correct methodological approach in sleep science studies. To make an evidence-based clinical decision, an appropriate control group is required to establish a valid asso-ciation between the risk factor/treatment and the outcome of an analytical sleep study. However, defining and recruiting healthy sleepers can be challenging for sleep researchers.